INITIATION OF BASKETBALL BY CATEGORY SUB IN PERSPECTIVE PLAYFUL-10 FOR STUDENTS OF PUBLIC SCHOOLS DISTRICT OF THE CITY OF JARAGUÁ MACEIÓ (Fiep Bulletin - online, 2016)
The main objective of this article is to present the Basketball through a playful approach to public school students in the neighborhood of Jaraguá. Therefore, a questionnaire was conducted with 5 (five) questions and it was applied to 20 (twenty) students between boys and girls from public schools in the district of Jaraguá to collect data. Through these experimental procedures, it is concluded that physical education classes taught in schools in the district of Jaraguá sometimes do not meet their real purposes like socializing and interdisciplinary, the effect being the need for inclusion of recreational activities. The fun, games and others activities including the effective participation of the students are of great importance in this process.
Keywords: Physical Education. Basketball. Playful.